2009
DOI: 10.1111/j.1365-2826.2009.01836.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gonadotrophin‐Releasing Hormone Pulse Generator Activity by the Pheromone in Small Ruminants

Abstract: In small ruminants, such as goats and sheep, a primer pheromone produced by males induces an out‐of‐seasonal ovulation in anoestrous females, a phenomenon known as the male effect. The male effect is unique in that an external chemical stimulus can immediately modulate the activity of the hypothalamic gonadotrophin‐releasing hormone (GnRH) pulse generator. We have established a monitoring method of the GnRH pulse generator activity in Shiba goat. Using this method as a sensitive bioassay to assess the male eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…57 : 197-202, 2011) n goats and sheep, exposure of seasonally anestrous females to the primer pheromone secreted by sexually mature males results in an out-of-seasonal ovulation [1][2][3][4]. Since the initial endocrine event following reception of the pheromone is the stimulation of pulsatile luteinizing hormone (LH) secretion, it has been thought that the central target of the pheromone signal is the GnRH pulse generator [1,[3][4][5], i.e., the neural substrate that generates intermittent GnRH discharges into the portal vessels, thereby regulating pulsatile LH secretion into the peripheral circulation [6,7].Although the neural identity of the GnRH pulse generator per se was unclear, it was possible to measure its activity by recording multiple-unit activity (MUA) at the mediobasal hypothalamus. It has been demonstrated that electrophysiological manifestations of the GnRH pulse generator are represented as characteristic increases in MUA (MUA volleys) that are exclusively associated with LH pulses in the monkey [8], rat [9] and goat [10,11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…57 : 197-202, 2011) n goats and sheep, exposure of seasonally anestrous females to the primer pheromone secreted by sexually mature males results in an out-of-seasonal ovulation [1][2][3][4]. Since the initial endocrine event following reception of the pheromone is the stimulation of pulsatile luteinizing hormone (LH) secretion, it has been thought that the central target of the pheromone signal is the GnRH pulse generator [1,[3][4][5], i.e., the neural substrate that generates intermittent GnRH discharges into the portal vessels, thereby regulating pulsatile LH secretion into the peripheral circulation [6,7].Although the neural identity of the GnRH pulse generator per se was unclear, it was possible to measure its activity by recording multiple-unit activity (MUA) at the mediobasal hypothalamus. It has been demonstrated that electrophysiological manifestations of the GnRH pulse generator are represented as characteristic increases in MUA (MUA volleys) that are exclusively associated with LH pulses in the monkey [8], rat [9] and goat [10,11].…”
mentioning
confidence: 99%
“…57: [197][198][199][200][201][202]2011) n goats and sheep, exposure of seasonally anestrous females to the primer pheromone secreted by sexually mature males results in an out-of-seasonal ovulation [1][2][3][4]. Since the initial endocrine event following reception of the pheromone is the stimulation of pulsatile luteinizing hormone (LH) secretion, it has been thought that the central target of the pheromone signal is the GnRH pulse generator [1,[3][4][5], i.e., the neural substrate that generates intermittent GnRH discharges into the portal vessels, thereby regulating pulsatile LH secretion into the peripheral circulation [6,7].…”
mentioning
confidence: 99%
“…The indirect use of a photoperiod to control the sexual activity of females by means of sexually active males is a sustainable breeding technique for goat reproduction in the subtropics. The high response induced by the light-treated males could be due to the fact that photoperiodic treatment stimulates testosterone secretion, the odor of males and their sexual behavior, improving the quality of signals provided by the males to does during the 'male effect' (Delgadillo et al, 2006;Murata Months Figure 6 Changes (mean 6 s.e.m.) in plasma testosterone concentrations in local male goats from subtropical Mexico subjected to natural photoperiodic variations (J, or to 2.5 months of artificial long days (16 h of light/day) from November 1, and then treated with two s.c. melatonin implants (n) or exposed to natural short days (') (adapted from Delgadillo et al (2002)).…”
Section: Control Of the Sexual Activity Of Male And Female Goatsmentioning
confidence: 99%
“…In sheep and goats, the seasonally anestrous endocrine state of females is changed to the estrous state upon exposure to male scents [7,8]. This so-called ''male effect'' is one of the most conspicuous primer pheromone effects in mammals [9,10]. In this study, we have identified an olfactory signal molecule that activates the central regulator of reproduction, the gonadotropinreleasing hormone (GnRH) pulse generator, in goats.…”
mentioning
confidence: 92%